Physicochemical Performance of Portland-Rice Husk Ash-Calcined Clay-Dried Acetylene Lime Sludge Cement in Sulphate and Chloride Media - Jackson Muthengia Wachira; Joseph Karanja Thiong’o; Joseph Mwiti Marangu; Leonard Genson Murithi (Advances in Materials Science and Engineering)
This paper reports leach and/or intake of SO42−, Cl−, Ca2+, Na+, and K+ from and/or into cement mortar cubes made from a novel cementious material in naturally encountered environmental simulated media. The paper also reports changes in pH of the media over time of exposure to the cement mortar cubes. The compressive strength changes of the test cement in simulated media are also reported. The novel cement, labelled PCDC, made from intermixing ordinary Portland cement (OPC) with waste materials which included rice husks, waste bricks, acetylene lime sludge, and spent bleaching earth was previously tested and found to meet the Kenyan Standard requirements for Portland pozzolana cement (PPC). 100 mm mortar cubes were prepared, and their compressive strengths were determined after exposure to the sea water. The media included sea water, distilled water, and solutions of sulphates and chlorides separately for a period of six months. The tests were carried alongside commercial PPC and OPC. The results showed that the PCDC exhibited comparable selected ions intake and/or leach to PPC in sea water, sulphate solutions, and distilled water. In chloride solutions, the cement exhibited the highest leach in the selected ions except K+ and Na+ ions. The results further showed that PCDC exhibited lower pH in all the media compared to OPC and PPC. The tests showed that the novel cement can be used for general construction work in the tested media in a similar manner to PPC.